TRANSFORMASI DIGITAL DALAM PENDIDIKAN ISLAM NONFORMAL DI LINGKUNGAN PERKANTORAN BUMN WIKA : INTEGRASI ARTIFICIAL INTELLIGENCE, BIG DATA, DAN PEMBELAJARAN IMERSIF MENUJU INDONESIA EMAS 2045 - Amad Chumsoni; Oki Setiana Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The acceleration of digital transformation has fundamentally changed the paradigm of educational management, including Islamic non-formal education within corporate environments. This study aims to analyze the strategic role of digital transformation through the integration of Artificial Intelligence (AI), Big Data Analytics, Blockchain, and immersive learning technologies in strengthening Islamic education programs within the State-Owned Enterprise (BUMN) environment, particularly at WIKA. This research employs a qualitative approach using library research methods by reviewing relevant scientific literature, policy documents, and contemporary studies on digital education and Islamic educational management. The findings reveal that digital transformation provides significant opportunities to improve the effectiveness, accessibility, accountability, and sustainability of Islamic educational activities in the workplace. The integration of AI enables personalized learning experiences, Big Data supports evidence-based decision-making, Blockchain enhances transparency and trustworthiness of educational records, while immersive technologies such as Virtual Reality (VR) and Augmented Reality (AR) strengthen experiential learning processes. Furthermore, the study proposes a Digital Islamic Learning Ecosystem model that integrates technological innovation with Islamic values including Amanah, Syura, Itqan, and Adl. The study concludes that digital transformation in Islamic non-formal education should not merely focus on technological adoption but must serve as a strategic instrument for developing spiritually resilient, digitally literate, and globally competitive human resources in support of Indonesia Emas 2045.